Prevalence of Exclusive Breast Feeding and Its Determinants: A Cross Sectional Study in District- Etawah, Uttar Pradesh - Anand M Dixit; Peeyush Kariwala; Pankaj Kumar Jain (Medsci Publications, 2017)
Back ground: Exclusive breast feeding is key for the proper growth and development of young infants. In spite of all benefits prevalence of exclusive breast feeding in our country is only 54.9 % as per national family health survey-4(2015-16). Various social customs and misconception act as barrier to breast feeding. This study was designed to find out prevalence and correlated variables in Etawah district Methodology: To access the prevalence and determinants of exclusive breast feeding a community based cross sectional study conducted in Etawah District. Information was collected from 300 mothers having infants less than six month of age. Binary logistic regression analysis was done to find out independent association of variables. Result: Prevalence of exclusive breast feeding was 52.3%. Prevalence decreases on addition of each month of life of infants. Education, Rural residence and Counselling show the positive relation with EBF. The major reason for starting top feeding is the belief of 33% mothers that their breast milk not enough for baby. Conclusion: In this area, Exclusive breast feeding still low in practice. This study emphasizes the need to address the problem related with EBF.